Control interno al área de producción y su incidencia en la rentabilidad de la embotelladora y purificadora de agua Manosalvas, cantón El Empalme, período 2012. - Álvarez García, Katheryne Zulay (2015)
The work involves the application of internal control to the production area of the bottling and Purifier Manosalvas, the Canton El Empalme, during the period 2012. The main objective is to determine the incidence of internal control in profitability company to do so, by the internal control is to guide the employer to take appropriate processes with effective strategies to achieve the objectives and targets set decisions. During the preparation of the thesis goals they helped determine a process of clear and effective audit for the purposes described in the main objective raised. The study of similar issues contributed to the understanding of the work to be done, using a methodology that helped describe the problems of the present investigation. The internal control audit was performed by applying orderly processes that serve to a better understanding of the implementation of the procedures. The results showed significant deficiencies in the company, starting with the low reliability of financial reporting, accounting due to ignorance that has staff working in the administrative area, which incurred in the preparation of poor financial reports that do not help make decisions suitable. The application of internal control procedures does not help the business operation to achieve the objectives and goals, and shows poor compliance with laws and regulations. The conclusions and recommendations described are addressed in the entrepreneurship and risk minimization actions that contribute to the growth of the company.